Exact Travelling Wave Solutions for Isothermal Magnetostatic Atmospheres by Fan Subequation Method. (4th December 2012) - Jafari, Hossein; Ghorbani, Maryam; Khalique, Chaudry Masood
Abstract : The equations of magnetohydrostatic equilibria for a plasma in a gravitational field are investigated analytically. An investigation of a family of isothermal magnetostatic atmospheres with one ignorable coordinate corresponding to a uniform gravitational field in a plane geometry is carried out. These equations transform to a single nonlinear elliptic equation for the magnetic vector potential u . This equation depends on an arbitrary function of u that must be specified. With choices of the different arbitrary functions, we obtain analytical solutions of elliptic equation using the Fan subequation method.